Improving the wet strength of hemicelluloses based composite films by citric acid crosslinking. (1st January 2021) - Li, Jiaoyang; Liu, Yuxin; Sun, Bing; Zhang, Renfeng
Abstract: In the present work, bagasse hemicelluloses were crosslinked using citric acid as a nontoxic crosslinking agent to improve the wet strength of hemicelluloses/SPI composite films at moderate relative humidity (RH). Fourier transform infrared and thermal analysis confirmed the formation of ester crosslinks between hemicelluloses and citric acid and led to lower the degradation temperature. The wet tensile strength properties of the citric acid crosslinked hemicelluloses/SPI films in 50 − 95% RH was improved significantly, compared to the uncross-linked films. Particularly, the results indicated that the films crosslinked under 0.44 degrees of substitution showed the best comprehensive properties among all films. However, excessive addition of citric acid in the composite films might decrease the compatibility of the films and have negative effects on their performance. This study provides an effective pathway for preparation of hemicelluloses/SPI composite films with improved wet strength properties, which have a potential as packaging material for food application. Graphical Abstract: